2016
DOI: 10.3390/ijerph13111104
|View full text |Cite
|
Sign up to set email alerts
|

Secular Trends in Growth and Nutritional Outcomes of Children under Five Years Old in Xiamen, China

Abstract: Abstract:The purpose of this study was to examine secular changes in growth and nutritional outcomes of Chinese urban children under five years old, in 2009, 2012, and 2015. Cluster random sampling methods were used to select children under five years old in Xiamen, one of five special economic zones in China. Subjects (N = 71,229) under five years old (39,413 boys, 31,816 girls) were examined at three different times (22,576 in 2009, 24,816 in 2012, and 23,837 in 2015). Significant differences in the boys' he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 24 publications
0
9
0
2
Order By: Relevance
“…Chen et al collected the anthropometry data of 71,229 children aged 0–5 years at three time points: 2009, 2012 and 2015 in Xiamen, a southeast city of China, and reported that the prevalence of obesity (defined as BMI for age ≥ P95) increased significantly from 0.9% in 2009 to 1.5% in 2015 among boys and from 0.8% to 1.3% among girls. They also reported that the prevalence of overweight (defined as BMI for age ≥ P85) increased significantly from 1.5% in 2009 to 6.5% in 2015 among boys and from 1.0% to 6.1% among girls [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chen et al collected the anthropometry data of 71,229 children aged 0–5 years at three time points: 2009, 2012 and 2015 in Xiamen, a southeast city of China, and reported that the prevalence of obesity (defined as BMI for age ≥ P95) increased significantly from 0.9% in 2009 to 1.5% in 2015 among boys and from 0.8% to 1.3% among girls. They also reported that the prevalence of overweight (defined as BMI for age ≥ P85) increased significantly from 1.5% in 2009 to 6.5% in 2015 among boys and from 1.0% to 6.1% among girls [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, our results showed a continually increasing trend of combined overweight and obesity in children aged 0–6 years in Harbin, a northeast city of China. A study from a southern city of China (Xiamen) also showed an increasing trend of combined overweight and obesity in children aged 0–5 years [ 17 ]. It indicated there are regional disparities in the trends in combined prevalence of overweight and obesity, so it is necessary to take interventions during early childhood, in order to control the increasing trend of combined overweight and obesity in adolescents and adults in the areas with similar increasing trend.…”
Section: Discussionmentioning
confidence: 99%
“…Âûÿâëåííàÿ äèíàìèêà â öåëîì ñîîòâåòñòâóåò ãëîáàëüíîé òåíäåíöèè ñòàáèëèçàöèè ïðîäîëüíîãî ðîñòà è ñðîêîâ ïîëîâîãî ñîçðåâàíèÿ â ñî÷åòàíèè ñ ñóùåñòâåííûì óâåëè÷åíèåì ìàññû òåëà è aeèðîîòëîaeåíèÿ, ôèêñèðóåìîé â íà÷àëå XXI âåêà â áîëüøèíñòâå ñòðàí ìèðà è íàçâàííîé «ýïèäåìèåé îaeèðåíèÿ».  ðÿäå ñîâðåìåííûõ ìèðîâûõ èññëåäîâàíèé ïîêàçàí íåãàòèâíûé ñ ôèçèîëîãè÷åñêîé òî÷êè çðåíèÿ òðåíä ñåêóëÿðíîãî óâåëè÷åíèÿ èíäåêñà ìàññû òåëà è ïðîöåíòà äåòåé ñ ðèñêîì îaeèðåíèÿ äëÿ ðàçíûõ ðåãèîíîâ: â Ñëîâåíèè [Tomac et al, 2012], ïîëüñêîì Êðàêîâå [Kryst et al,2012]; Íèäåðëàíäàõ [Hirasing et al, 2001] è äðóãèõ ñòðàíàõ Çàïàäíîé Åâðîïû [Wang , Lobstein, 2006], äëÿ ãîðîäñêèõ äåòåé, â ìåíüøåé ñòåïåíè ñåëüñêèõ, Þaeíîé Ìåêñèêè [Malina et al, 2008], ñîâðåìåííîì Êèòàå [Chen et al, 2016], Ðîññèè [Ðàçèíà ñ ñîàâò., 2016;Rtveladze et al, 2012]. Êàòàñòðîôè÷åñêîå óñèëåíèå ðàçâèòèÿ aeèðîîòëîaeåíèÿ ïðîèñõîäèò íà ôîíå óñèëåíèÿ «îáåñîãåííîñòè» ñðåäû (îò obesogenicïðîâîöèðóþùåé îaeèðåíèå), â êà÷åñòâå ôàêòîðîâ îáåñîãåííîñòè â ïåðâóþ î÷åðåäü íàçûâàþò äàëåêóþ îò èäåàëà ñòðóêòóðó ïèòàíèÿ, ãèïîäèíàìèþ è øèðîêîå ðàñïðîñòðàíåíèå ãîðîäñêîãî îáðàçà aeèçíè, êàê ñëåäñòâèå -òåõíîãåííîå çàãðÿçíåíèå ñðåäû.…”
unclassified
“…The external environment of economic zones, referring to all the external factors and conditions that can have an effect and influence on the system, generally includes political, economic, cultural and ecological conditions from the regional, national and international levels. Thus, as a kind of economic system with specific structure, economic zone system reflects its economic, environmental and technological functions via input-output form, which transfer intelligence, money and other resources into the developing outcomes of economy, society and technology [ 5 , 6 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, with the accelerating pace of economic globalization and the further deepening of China’s reform and opening up, China’s economic zones undertake an important responsibility and face huge pressures from external and internal directions [ 5 , 6 ]. Transformation and selecting the development direction of economic zones is also difficult.…”
Section: Introductionmentioning
confidence: 99%